The Positive Impact of Joint Activities on Students Attitudes Toward Peers With Disabilities - Alnahdi, Ghaleb H.; Schwab, Susanne; Elahdi, Ayman; Alnahdi, Aminah H. (Frontiers in Psychology, 2021)
Background: Attitudes toward peers with disabilities play a crucial role in implementing inclusive education. This study examines how students' attitudes are associated with gender; having relatives with disabilities and the frequency of contact with them; attending a class that includes students with special educational needs (SEN); and having previous contact with SEN students through joint activities. Methods and Procedures: The participants included 652 elementary school students (grades 4–6) who completed a short version of the Chedoke-McMaster Attitudes Toward Children with Handicaps (CATCH) questionnaire in Arabic. Outcomes and Results: Students in inclusive classes express more positive attitudes in comparison with students in regular classes. However, previous contact through joint activities was associated with more positive attitudes. Females were more likely to hold positive views than males. Having relatives with disabilities had no effect; however, a high frequency of contact with them was associated with more positive perspectives. Conclusions and Implications: The findings on students' attitudes indicate that joint activities between students with and without disabilities are important to promote positive attitudes. Planned opportunities to increase frequent contact, and to promote joint activities between students with and without SEN are recommended.